Die „hohe Politik“ und der „tanzende Kongress“. Die Wahrnehmung des Wiener Kongresses durch die damaligen Zeitgenossen - Martin Fritz (Historia.scribere)
This paper reviews the legal foundations of work-related migration to Germany and Austria in the second half of the 20th century. Three key questions frame the analysis: at the beginning an overview shows which legal regulations are being made and by whom. This first step is to trace the actors behind the laws and to analyze their contents. Secondly historical continuities that could lead to a postcolonial perspective are being examined. The concluding third step outlines the gap between legal norms and reality, thereby aiming at sensitizing for the political-economic motives and every-day-reality as well as normative ideologies.